Maze of Doom ; The Haunting of Spook House. - Ivanoff, George (North Sydney, N.S.W Random House Australia, 2015)
Two action-packed stories, hundreds of different endings! This volume contains books three and four of the series, bound in tete-beche format. Find your way through a maze without being killed, and survive the angry ghosts in spook house!
Keywords: Haunted houses -- Labyrinths -- Children's stories